The Role of Education in Household Food Waste Behavior among Resource-Constrained Households - Yayuk Farida Baliwati; Prita Dhyani Swamilaksita; Drajat Martianto; Dodik Briawan (Media Gizi Indonesia, 2026)
Background: Household food waste may occur even in resource-constrained households, creating a paradox in which food waste coexists with inadequate energy consumption. Understanding the structural, psychosocial, and behavioral determinants of food waste is essential for developing effective interventions. Objective: This study aimed to examine the role of structural, psychosocial, and food management behavioral factors associated with household food waste and energy consumption among low-income households. Methods: A cross-sectional study was conducted among 100 low-income households. Structural characteristics, psychosocial factors based on the Theory of Planned Behavior (TPB), and food management behaviors were assessed using structured questionnaires. Household food waste was recorded for eight consecutive days, while energy consumption was evaluated using energy adequacy levels. Data were analyzed using chi-square tests and logistic regression. Results: Food waste was identified in all households, while 63.4% experienced energy deficits. Educational attainment was the only structural factor significantly associated with lower household food waste. Psychosocial factors were not significantly associated with either food waste or energy consumption. Food storage practices were associated with energy consumption in the bivariate analysis but were not retained as significant predictors in the multivariate model. Conclusion: Household food waste in resource-constrained households is influenced primarily by structural factors, particularly educational attainment. Strengthening food literacy through practical educational interventions may contribute to reducing household food waste and improving food security.